2016
DOI: 10.1002/jtr.2076
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Smartphone Usage among Tourists

Abstract: We explore smartphone utilization by tourists from 24 countries visiting either Rome, Italy or Athens, Greece. By extending a standard technology acceptance model, we identify common travel uses for smartphones, which include taking photos, social networking, viewing maps, finding transportation and searching for shops and restaurants. Younger cohorts utilize their phones more than older cohorts, but there is no difference in utilization between females and males. The most important factors affecting behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 27 publications
8
27
2
1
Order By: Relevance
“…People who are more accustomed to using their phones at home have more interest in doing so while traveling, and are more likely to do so [38,39]. This helps them save time [40], and therefore influences both their satisfaction and the relationship between mobility and satisfaction [41].…”
Section: Sustainable Smart Tourism Destinationsmentioning
confidence: 99%
“…People who are more accustomed to using their phones at home have more interest in doing so while traveling, and are more likely to do so [38,39]. This helps them save time [40], and therefore influences both their satisfaction and the relationship between mobility and satisfaction [41].…”
Section: Sustainable Smart Tourism Destinationsmentioning
confidence: 99%
“…IPhone and Blackberry are the most popular brands, while the most widely operation system recorded in the World was the Android. Mang et al (2016) reported that consumers for mobile phones at developed and high growth emerging economics are increasing and through which, there is a clear rise in the percentage of smartphones' owners.…”
Section: Smart Phone Technologymentioning
confidence: 99%
“…While the dynamic displays that digital maps afford are incredibly powerful, paper maps retain certain advantages. For instance, paper maps do not require power; their light weight can make them more portable than digital maps on mobile devices [22], their large display sizes relative to mobile maps support certain activities better [5,15], such as collaboration [2]; they can be cheaper when engaging in foreign travel due to roaming costs [17]; and they can be easier to customize while in the field [22]. Hurst et al [14] showed that geographic knowledge and the context of use influenced whether users preferred paper or digital media: as geographic skills increase, there is a greater preference for paper maps, while non-experts prefer digital maps.…”
Section: Paper and Digital Media For Cartographymentioning
confidence: 99%